RELIGIUSITAS DALAM PERSPEKTIF ISLAM: Suatu Kajian Psikologi Agama - S Safrilsyah; Rozumah Baharudin; Nurdeng Duraseh (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2010)
The religious values that have been embedded in human’s soul which played a major role in the development of human’s character. So that, many religions teach virtue, a short of the reflection of the ideals to make happen people honest and pious in their life. A number researches have been conducted among western people specially on non moslem but in many ways need to be adjusted in the context of Muslim society. As the result, the concept of religiosity that Western researchers developed still are not applicable with eastern cultures which are more transcendent.  Since the study of religiosity in the context of Eastern community is still in limited amounts, therefore this paper seeks to enrich the number of works on religiousity specially in Islamic perspective.  Islam is a rational, practical and con-prehensif religion. Ansari (in Ancok), states that Islam is basically divided into three dimensions, namely faith (Islam), religious (sharia) and morality (Ihsan), in which three parts were interconnected with each other